Evaluate the expression, \[\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\sqrt{3+2x}-
(\sqrt{2}+1)}{{{x}^{2}}-2}\]
Answer
Verified
513k+ views
Hint: First check if the limit has an indeterminate form. If it does, only then move on to applying the L’ Hopital Rule.
The given equation is;
\[\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\sqrt{3+2x}-(\sqrt{2}+1)}{{{x}^{2}}-2}\]
Firstly, let’s check if the given limit evaluates to an indeterminate form when we put
$x=\sqrt{2}$. Let’s do that now. Doing so, we’ll have to put $x=\sqrt{2}$ in the expression
\[\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\sqrt{3+2x}-(\sqrt{2}+1)}{{{x}^{2}}-2}\]
\[\to \dfrac{\sqrt{3+2\sqrt{2}}-\left( \sqrt{2}+1 \right)}{\left( {{x}^{2}}-2 \right)}\]
\[\to \dfrac{\sqrt{3+2\sqrt{2}}-\left( \sqrt{2}+1 \right)}{0}\]
Here, we can clearly see that the denominator does equate to zero on putting the limiting value
of $x$.
Now, the numerator doesn’t look like it evaluates to zero, right ? Let’s try manipulating the
numerator alone, after we put the value $x=\sqrt{2}$ in it.
Thus, we have $\sqrt{3+2\sqrt{2}}-(\sqrt{2}+1)$
$\to \sqrt{2+1+2\sqrt{2}}-\left( \sqrt{2}+1 \right)$
$\to \sqrt{{{\left( \sqrt{2} \right)}^{2}}+{{1}^{2}}+2\sqrt{2}}-\left( \sqrt{2}+1 \right)$
The first term looks similar to the identity $\left( {{a}^{2}}+{{b}^{2}}+2ab \right)={{\left( a+b
\right)}^{2}}$
$\to \sqrt{{{\left( \sqrt{2}+1 \right)}^{2}}}-\left( \sqrt{2}+1 \right)$
$\to{\left( \sqrt{2}+1 \right)}-{\left( \sqrt{2}+1 \right)}=0$
That becomes $0$. Hence the numerator also evaluates to zero on putting the limiting value of
$x$ in it.
Thus, we now can confirm that the limit ultimately evaluates to a $\dfrac{0}{0}$ form. Hence, it
fulfils the condition of using the L’ Hopital Rule, since the rule needs that the limit evaluates to
a $\dfrac{0}{0}$ or an $\dfrac{\infty }{\infty }$ form.
Now, by using L’HOPITAL RULE, i.e., the limit of a function evaluating to a $\dfrac{0}{0}$ or an
$\dfrac{\infty }{\infty }$ form, can be found out by separately differentiating the numerators
and denominators in terms of the variable that has the limit attached to it, successively, till the
indeterminate form goes away.
Thus, we’ll apply L’ Hopital Rule for the first time now.
Therefore, $\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\dfrac{d(\sqrt{3+2x}-
(\sqrt{2}+1))}{dx}}{\dfrac{d({{x}^{2}}-2)}{dx}}$
By power rule & chain rule, we get;
$\to \underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{1}{2\sqrt{3+2x}}.\dfrac{2-0}{2x-0}$
$\to \underset{x\to \sqrt{2}}{\mathop{\lim
}}\,\dfrac{\dfrac{1}{{2}\sqrt{3+2x}}.{2}-0}{2x-0}$
$\to \underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{1}{2x\sqrt{3+2x}}$
Now, putting the limits, we get;
$\to \dfrac{1}{2\sqrt{2}\left( \sqrt{3+2\sqrt{2}} \right)}$
$\to \dfrac{1}{2\sqrt{2}\sqrt{{{\left( \sqrt{2} \right)}^{2}}+{{1}^{2}}+2\sqrt{2}}}$
$\to \dfrac{1}{2\sqrt{2}\sqrt{{{\left( \sqrt{2}+1 \right)}^{2}}}}$
$\to \dfrac{1}{2\sqrt{2}\left( \sqrt{2}+1 \right)}$
$\to \dfrac{1}{4+2\sqrt{2}}$
Now, we will do rationalisation. Let’s multiply the numerator and denominator by the
conjugate of $4+2\sqrt{2}$. That means, we multiply numerator and denominator with $4-
2\sqrt{2}$. Doing so, we get:
$\to \dfrac{1}{\left( 4+2\sqrt{2} \right)}\times \dfrac{\left( 4-2\sqrt{2} \right)}{\left( 4-2\sqrt{2}
\right)}$
$\to \dfrac{4-2\sqrt{2}}{{{4}^{2}}-{{\left( 2\sqrt{2} \right)}^{2}}}$
$\to \dfrac{4-2\sqrt{2}}{16-8}$
$\to \dfrac{4-2\sqrt{2}}{8}$
$\to \dfrac{2-\sqrt{2}}{4}$
Hence, the solution for the equation is $\dfrac{2-\sqrt{2}}{4}$.
Note: Always check first by putting limits, if the limit evaluates to an indeterminate form, and
then, remember L-HOSPITAL RULE :
i.e., $\underset{x\to a}{\mathop{\lim }}\,\dfrac{f(x)}{g(x)}=\underset{x\to a}{\mathop{\lim
}}\,\dfrac{f'(x)}{g'(x)}=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f''(x)}{g''(x)}=.....$, till the limit
loses its indeterminate form.
The given equation is;
\[\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\sqrt{3+2x}-(\sqrt{2}+1)}{{{x}^{2}}-2}\]
Firstly, let’s check if the given limit evaluates to an indeterminate form when we put
$x=\sqrt{2}$. Let’s do that now. Doing so, we’ll have to put $x=\sqrt{2}$ in the expression
\[\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\sqrt{3+2x}-(\sqrt{2}+1)}{{{x}^{2}}-2}\]
\[\to \dfrac{\sqrt{3+2\sqrt{2}}-\left( \sqrt{2}+1 \right)}{\left( {{x}^{2}}-2 \right)}\]
\[\to \dfrac{\sqrt{3+2\sqrt{2}}-\left( \sqrt{2}+1 \right)}{0}\]
Here, we can clearly see that the denominator does equate to zero on putting the limiting value
of $x$.
Now, the numerator doesn’t look like it evaluates to zero, right ? Let’s try manipulating the
numerator alone, after we put the value $x=\sqrt{2}$ in it.
Thus, we have $\sqrt{3+2\sqrt{2}}-(\sqrt{2}+1)$
$\to \sqrt{2+1+2\sqrt{2}}-\left( \sqrt{2}+1 \right)$
$\to \sqrt{{{\left( \sqrt{2} \right)}^{2}}+{{1}^{2}}+2\sqrt{2}}-\left( \sqrt{2}+1 \right)$
The first term looks similar to the identity $\left( {{a}^{2}}+{{b}^{2}}+2ab \right)={{\left( a+b
\right)}^{2}}$
$\to \sqrt{{{\left( \sqrt{2}+1 \right)}^{2}}}-\left( \sqrt{2}+1 \right)$
$\to{\left( \sqrt{2}+1 \right)}-{\left( \sqrt{2}+1 \right)}=0$
That becomes $0$. Hence the numerator also evaluates to zero on putting the limiting value of
$x$ in it.
Thus, we now can confirm that the limit ultimately evaluates to a $\dfrac{0}{0}$ form. Hence, it
fulfils the condition of using the L’ Hopital Rule, since the rule needs that the limit evaluates to
a $\dfrac{0}{0}$ or an $\dfrac{\infty }{\infty }$ form.
Now, by using L’HOPITAL RULE, i.e., the limit of a function evaluating to a $\dfrac{0}{0}$ or an
$\dfrac{\infty }{\infty }$ form, can be found out by separately differentiating the numerators
and denominators in terms of the variable that has the limit attached to it, successively, till the
indeterminate form goes away.
Thus, we’ll apply L’ Hopital Rule for the first time now.
Therefore, $\underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{\dfrac{d(\sqrt{3+2x}-
(\sqrt{2}+1))}{dx}}{\dfrac{d({{x}^{2}}-2)}{dx}}$
By power rule & chain rule, we get;
$\to \underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{1}{2\sqrt{3+2x}}.\dfrac{2-0}{2x-0}$
$\to \underset{x\to \sqrt{2}}{\mathop{\lim
}}\,\dfrac{\dfrac{1}{{2}\sqrt{3+2x}}.{2}-0}{2x-0}$
$\to \underset{x\to \sqrt{2}}{\mathop{\lim }}\,\dfrac{1}{2x\sqrt{3+2x}}$
Now, putting the limits, we get;
$\to \dfrac{1}{2\sqrt{2}\left( \sqrt{3+2\sqrt{2}} \right)}$
$\to \dfrac{1}{2\sqrt{2}\sqrt{{{\left( \sqrt{2} \right)}^{2}}+{{1}^{2}}+2\sqrt{2}}}$
$\to \dfrac{1}{2\sqrt{2}\sqrt{{{\left( \sqrt{2}+1 \right)}^{2}}}}$
$\to \dfrac{1}{2\sqrt{2}\left( \sqrt{2}+1 \right)}$
$\to \dfrac{1}{4+2\sqrt{2}}$
Now, we will do rationalisation. Let’s multiply the numerator and denominator by the
conjugate of $4+2\sqrt{2}$. That means, we multiply numerator and denominator with $4-
2\sqrt{2}$. Doing so, we get:
$\to \dfrac{1}{\left( 4+2\sqrt{2} \right)}\times \dfrac{\left( 4-2\sqrt{2} \right)}{\left( 4-2\sqrt{2}
\right)}$
$\to \dfrac{4-2\sqrt{2}}{{{4}^{2}}-{{\left( 2\sqrt{2} \right)}^{2}}}$
$\to \dfrac{4-2\sqrt{2}}{16-8}$
$\to \dfrac{4-2\sqrt{2}}{8}$
$\to \dfrac{2-\sqrt{2}}{4}$
Hence, the solution for the equation is $\dfrac{2-\sqrt{2}}{4}$.
Note: Always check first by putting limits, if the limit evaluates to an indeterminate form, and
then, remember L-HOSPITAL RULE :
i.e., $\underset{x\to a}{\mathop{\lim }}\,\dfrac{f(x)}{g(x)}=\underset{x\to a}{\mathop{\lim
}}\,\dfrac{f'(x)}{g'(x)}=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f''(x)}{g''(x)}=.....$, till the limit
loses its indeterminate form.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE